Development of Enthesopathies and Joint Structural Damage in a Murine Model of X-Linked Hypophosphatemia - Faraji-Bellée, Carole-Anne; Cauliez, Axelle; Salmon, Benjamin; Fogel, Olivier; Zhukouskaya, Volha; Benoit, Aurélie; Schinke, Thorsten; Roux, Christian; Linglart, Agnès; Miceli-Richard, Corinne; Chaussain, Catherine; Briot, Karine; et al. (Frontiers in Cell and Developmental Biology, 2020)
X-linked hypophosphatemia (XLH) is characterized by rickets and osteomalacia, caused by inactivating mutations in the Phosphate-regulating endopeptidase homolog X-linked (PHEX) gene. With aging, adult patients develop paradoxical heterotopic calcifications of tendons and ligaments at their insertion sites (enthesophytes), and joint alterations. Understanding the progression of this structural damage that severely affects patients’ quality of life will help to improve the management of XLH. Here, we characterized the occurrence of enthesophytes and joint alterations through a 12-month in vivo micro-CT follow-up in the Hyp mouse, a murine model of XLH (n=5 mice per group). Similar to adult patients with XLH, Hyp mice developed calcaneal enthesophytes, hip joint alterations, erosions of the sacroiliac joints and periarticular calcifications. These lesions were already present at month 3 and gradually worsened over time. In sharp contrast, no abnormalities were observed in control mice at early time points. Histological analyses confirmed the presence of bone erosions, calcifications and expansion of mineralizing enthesis fibrocartilage in Hyp mice and their absence in controls and suggested that new bone formation is driven by altered mechanical strain. Interestingly, despite a strong deformation of the curvature, none of the Hyp mice displayed enthesophyte at the spine. Peripheral enthesophytes and joint alterations develop at the early stages of the disease and gradually worsen overtime. Overall, our findings highlight the relevance of this preclinical model to test new therapies aiming to prevent bone and joint complications in XLH.